Exposição de pacientes com síndrome de dor miofascial (SDM) à capsaicina: desenvolvimento de forma farmacêutica de uso tópico com possível ação analgésica - Motta, Valeria Romero Vieira da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Background and Objective: myofascial pain syndrome (MPS) is one of the most common causes of musculoskeletal pain. This pain may originate in a single muscle and eventually may involve multiple muscles generating complex patterns and variable painful symptoms. In this study capsaicin, a natural product obtained from red pepper, was formulated in a high concentration. Capsaicin, which has long been used for the management of pain, was tested as an alternative to the management of the MPS. The objective of this study was to develop and evaluate the potential analgesic action of a semi-solid formulation (cream) containing capsaicin 8% on myofascial pain syndrome patients. At the same time we evaluated the occurrence of cutaneous side effects related to the topic use of capsaicin, as well as the plasma capsaicin concentrations result of its use. Also the residual capsaicin concentration was tested in the formulations after 10 months of manufacturing. Methods: two formulations were developed: Fc1 (based cream formula) and Fc2 (cream formula base + capsaicin 8%). The formulations were submitted to microbiological tests, physical and chemical quality evaluation, as recommended by ANVISA. This prospective, randomized study was conducted in Pain Management and Palliative Care Service (TACP), Botucatu, Botucatu Medical School, UNESP. The 40 participating patients were assigned into two groups, Fc1 and Fc2. The clinical tests were carried out at the hospital; the creams were administered topically, as per assigned group, with the prior use of topical local anesthetic for 50 minutes. The trigger point (PG) that aroused more discomfort and pain on palpation was chosen for topical application of the formulations (10 g) in an enclosed area of about 24 mm and above this point. After 30 minutes the product was removed and parameters of the skin tolerability were evaluated. The pain was measured immediately before and during application of the ...

Introdução e Objetivo: a síndrome de dor miofascial (SDM) é uma das causas mais comuns de dor musculoesquelética. Esta dor pode se originar em um único músculo e, eventualmente, pode envolver múltiplos músculos gerando padrões complexos e variáveis de sintomas dolorosos. Nesta pesquisa, utilizou-se a capsaicina em alta concentração, produto natural obtido da pimenta vermelha e que há muito é empregada para o alívio da dor, como alternativa ao tratamento da SDM. Assim, o objetivo deste estudo foi desenvolver e avaliar a possível ação analgésica de uma forma farmacêutica semi-sólida (creme) de capsaicina 8% em pacientes com síndrome de dor miofascial. Paralelamente avaliou-se a ocorrência de efeitos de intolerância cutânea relacionados ao emprego tópico da capsaicina, bem como as concentrações de capsaicina plasmática e finais, após 10 meses de manufatura, nas formulações. Material e Métodos: foram desenvolvidas as formulações Fc1 (fórmula creme base) e Fc2 (fórmula creme base + capsaicina 8%). As mesmas foram submetidas aos ensaios microbiológicos, físicos e químicos para avaliação da qualidade, conforme preconizado pela ANVISA. Este estudo prospectivo e randomizado foi desenvolvido no Serviço de Terapia Antálgica e Cuidados Paliativos (TACP) da Faculdade de Medicina de Botucatu, UNESP. Os 40 pacientes participantes foram alocados em dois grupos, Fc1 e Fc2. Sempre em âmbito hospitalar, os cremes foram administrados topicamente, conforme o grupo, com o emprego prévio de anestésico local tópico por 50 minutos. Para tal, escolheu-se o pontogatilho (PG) que mais provocava desconforto e dor à palpação para a aplicação tópica das formulações na quantidade de 10 g em área delimitada de aproximadamente 24 mm e superficialmente a este ponto. Após 30 minutos da aplicação o produto foi retirado, tendo sido avaliados os parâmetros de tolerabilidade à pele. A dor foi quantificada imediatamente,...
Exposure of patients with myofascial pain syndrome (MPS) to capsaicin : development of pharmaceutical form for topical use with possible analgesic action
Keywords: Sindromes da dor miofacial; Dor facial; Músculos - Doenças; Alcalóides; Medicamentos - Administração; Capsaicina; Myofascial pain syndromes